(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article contains the analysis of works of scientists dedicated to the development of higher pedagogical education in Ukraine from 1985-to 2003. The main tendencies, directions, achievements, and problems of this development are characterized.